Exploring the Relationship between PheSA Scores and Ligand Efficiency in the Discovery of Potent Antimalarials: A Computational Perspective - Ayodele, Agede O.; Ayodele, Ogunmodede J.; Nasiru, Sanni; Musa, Wasagu I.; Sunday, Oyedepo Dapo; Stephen, Aiyedun Olawale; Olufunke, Falade C. (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2024)
Pharmacophore Enhanced Shape Alignment (PheSA) compares the similarities of compounds based on their pharmacophoric and geometrical characteristics. Ligand efficiency is a notion used to maximize the potency and effectiveness of medication candidates by taking into account their molecular weight and binding affinity. This study mainly focused on Cycloguanil analogues to evaluate the association between PheSA scores and ligand efficiency in the identification of effective antimalarials. Information on 36 PfDHFR inhibitors, their structures and biological activity was retrieved from the ChEMBL database. Based on shape and pharmacophore similarity, the PheSA algorithm was used to compare the 3D structures of the inhibitors. Based on a de novo synthesis method, 257 new compounds with greater PheSA similarity scores that have a striking resemblance to cycloguanil were created. The PheSA score and ligand efficiency have a moderately positive link (correlation coefficient of 0.675) according to the analysis. However, the virtual screening of cycloguanil analogues based on PheSA similarity scores offers a useful initial evaluation of structural similarity, directing further experimental studies to find interesting substances for the creation of effective antimalarial drug.